Optimal design of supplemental negative stiffness damped outrigger system for high-rise buildings resisting multi-hazard of winds and earthquakes - Wang, Meng; Nagarajaiah, Satish; Sun, Fei-Fei (Journal of wind engineering and industrial aerodynamics, 2021)
This paper deals with the multi-hazard vibration reduction of high-rise buildings in resisting earthquakes and winds, emphasizing on the optimization of supplemental negative stiffness damped outrigger (NSDO) system. Since the risks of wind and earthquake are both inevitable, the competing relationship between two performance indexes—harmful inter-story drift and structural acceleration—of tall buildings with supplemental NSDO are carefully studied concerning along wind, cross wind, and earthquake loading. As an energy dissipation outrigger system, NSDO amplifies the deformation of viscous damper at the outrigger ends, thus achieving higher efficiency as compared to conventional damped outrigger (CDO) systems. The resultant superiority of NSDO in resisting multi-hazard is then verified. For example, NSDO provides a further reduction of 25.6% in seismic harmful drift and an extra 22.3% decrease in cross wind acceleration response. In the meantime, NSDO only uses about 1/3 of the outrigger damping coefficient as compared to CDO systems. Moreover, NSDO optimized for multi-hazard can achieve a good tradeoff design without compromising too much for one specific hazard. •Optimizing negative stiffness damped outrigger (NSDO) systems in high-rise buildings concerning winds and earthquakes.•Competing relationships between harmful drift and acceleration subjected to multi-hazard are investigated.•Verifying the high efficiency of NSDO as compared with conventional damped outrigger in resisting multi-hazard.